2018
DOI: 10.1128/cmr.00045-17
|View full text |Cite
|
Sign up to set email alerts
|

Buruli Ulcer, a Prototype for Ecosystem-Related Infection, Caused by Mycobacterium ulcerans

Abstract: Buruli ulcer is a noncontagious disabling cutaneous and subcutaneous mycobacteriosis reported by 33 countries in Africa, Asia, Oceania, and South America. The causative agent, , derives from by genomic reduction and acquisition of a plasmid-borne, nonribosomal cytotoxin mycolactone, the major virulence factor. -specific sequences have been readily detected in aquatic environments in food chains involving small mammals. Skin contamination combined with any type of puncture, including insect bites, is the most p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(88 citation statements)
references
References 359 publications
(742 reference statements)
1
76
0
3
Order By: Relevance
“…The infection is self-limiting and several reports suggest the highest risk is associated with living in a riverine region [79e83]. As to the potential route for inoculation, several theories have been suggested such as bites from water bugs [84,85] and the potential for colonization with the bacterium through contact with soil [86] and watersheds [87,88].…”
Section: Mycobacterium Ulceransmentioning
confidence: 99%
“…The infection is self-limiting and several reports suggest the highest risk is associated with living in a riverine region [79e83]. As to the potential route for inoculation, several theories have been suggested such as bites from water bugs [84,85] and the potential for colonization with the bacterium through contact with soil [86] and watersheds [87,88].…”
Section: Mycobacterium Ulceransmentioning
confidence: 99%
“…Mycobacterium ulcerans is responsible for a chronic debilitating skin and soft tissue infection that can lead to permanent disfigurement and disability in mammals and humans for whom the so-called Buruli ulcer is the third worldwide most common mycobacterial disease after tuberculosis and leprosy (1). The ultimate environmental reservoir for M. ulcerans is unknown but M. ulcerans DNA sequences are commonly detected in water and moist soil as well as in biofilms associated to the surface of aquatic and terrestrial plants in endemic tropical countries (2).…”
Section: Importancementioning
confidence: 99%
“…Mycobacterium ulcerans is an environmental slowly growing, non-tuberculous mycobacterium responsible for progressively extending cutaneous and subcutaneous ulcer named Buruli ulcer [1]. Buruli ulcer is a World Health Organization-notifiable neglected infection which has been notified by 34 countries over the last ten years [2]. Accordingly, Buruli ulcer is a tropical infection mainly affecting rural populations in South America, West Africa, Australia, South-China and Japan [3].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, Buruli ulcer is a tropical infection mainly affecting rural populations in South America, West Africa, Australia, South-China and Japan [3]. Although a genetic trait has recently been described among a 7-individual family in whom two individuals suffered Buruli ulcer and carried a specific deletion on chromosome 8 [4], in addition to previously reported deletion in the NRAMP-1 gene [5], nevertheless Buruli ulcer is not a contagious infection but is rather resulting from contacts with M. ulcerans -contaminated environments [2]. Accordingly, it’s been reported that M. ulcerans is being cultivated from aquatic Hemiptera [6].…”
Section: Introductionmentioning
confidence: 99%